2005
DOI: 10.2337/diacare.28.1.95
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Role of Mean 24-h Pulse Pressure Level for Cardiovascular Events in Type 2 Diabetic Subjects Under 60 Years of Age

Abstract: OBJECTIVE -To assess the prognostic role of ambulatory 24-h pulse pressure (PP) on various vascular events in relatively young type 2 diabetic subjects under 60 years of age.RESEARCH DESIGN AND METHODS -In this prospective study, 237 type 2 diabetic subjects without any history of vascular complications were analyzed. After excluding 9 dropout subjects, 228 subjects (mean age, 46 years; 69% men; mean follow-up period, 100 months) entered the study.RESULTS -Distribution of 24-h PP for all subjects showed left s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 23 publications
5
28
1
Order By: Relevance
“…Although the crosssectional design did not allow any firm conclusions regarding causality, we hypothesised that PP could be a risk factor for the progression of albuminuria in this patient group. Subsequently, several studies have associated an elevated PP with both micro- [3,5] and macrovascular [6][7][8] complications in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the crosssectional design did not allow any firm conclusions regarding causality, we hypothesised that PP could be a risk factor for the progression of albuminuria in this patient group. Subsequently, several studies have associated an elevated PP with both micro- [3,5] and macrovascular [6][7][8] complications in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…An elevated pulse pressure (PP) is strongly associated with micro- [1][2][3][4][5] as well as macrovascular [1,[6][7][8] complications in type 2 diabetic patients. In a large observational study including 954 elderly type 2 diabetic patients [9], ambulatory PP was a strong and independent predictor of progression of nephropathy during a 2 year follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…12,14,15,24 Nakano et al 15 reported the highest quartile of 24-h PP to predict cardiac, but not cerebral, events in a cohort of 228 young (mean age 46 years) Japanese type 2 diabetic patients without a history of CVD. However, the ABPM measurements were performed during hospitalisation, thus raising the possibility of selection bias and limiting the reproducibility of the findings in a general setting.…”
Section: Effect Of Combined 10 Mmhg Increase In 24-h Pp Andmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] However, only a few BP parameters were evaluated in each of these studies and the potential interaction between BP parameters were not examined. Moreover, some studies report the association with total mortality, not with CV mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation